Being applied at rice or wheat season impacts biochar's effect on gaseous nitrogen pollutants from the wheat growth cycle. (1st August 2022) - Zhang, Yu; Jeyakumar, Paramsothy; Xia, Changlei; Lam, Su Shiung; Jiang, Jiang; Sun, Haijun; Shi, Weiming
Abstract: Biochar (BC) application to agricultural soil can impact two nitrogen (N) gases pollutants, i.e., the ammonia (NH3 ) and nitrous oxide (N2 O) losses to atmospheric environment. Under rice-wheat rotation, applied at which growth cycle may influence the aforementioned effects of BC. We conducted a soil column (35 cm in inner diameter and 70 cm in height) experiment to evaluate the responses of wheat N use efficiency (NUE), NH3 volatilization, and N2 O emission from wheat season to biochar applied at rice (R) or wheat (W) growth cycle, meanwhile regarding the effect of inorganic fertilizer N input rate, i.e., 72, 90, and 108 kg ha −1 (named N72, N90, and N108, respectively). The results showed that BC application influenced the wheat growth and grain yield. In particular, BC applied at rice season increased the wheat grain yield when receiving 90 and 108 kg N ha −1 . The improved wheat grain yield was attributed to that N90 + BC(R) and N108 + BC(R) enhanced the wheat NUE by 53.8% and 52.8% over N90 and N108, respectively. More N input led to higher NH3 volatilization and its emission factor. Interestingly, 19.7%–34.0% lower NH3 vitalizations were recorded under treatments with BC applied in rice season, compared with the treatments only with fertilizer N. BC applied at rice season exerted higher efficiency on mitigating N2 O emission than that applied at wheat season under three N input rates, i.e., 60.5%–77.6% vs 29.8%–34.8%. Overall, considering the crop yield and global warming potential resulting from NH3 volatilization and N2 O emission of wheat season, N90 + BC(R) is recommended. In conclusion, farmers should consider the application time and reduce inorganic fertilizer N rate when using BC. Graphical abstract: Image 1 Highlights: Biochar was applied at rice (BC-R) or wheat growth cycle (BC–W) with three N application rate. Biochar added at both crop seasons increased the wheat NUE under medium and high N treatments. BC decreased NH3 vitalization only when being applied at rice growth cycle. BC-R exerted higher mitigation efficiency on N2 O emission than BC-W.